La protection de la propriété terrienne entre loi et arbitrages - Ahmad Reza Sadeghi (Revue des Mondes Musulmans et de la Méditerranée)
Legal conflicts in Afghanistan relating to real property are handled in one of two ways: through informal, customary means, or through formal, institution-based means. The former appears to be more credible than the latter, with eighty percent of cases being resolved informally. Nevertheless, both of these possible avenues present numerous difficulties. Violations of real property rights are not sufficiently penalized under the penal code of the official legal system. Penalties under that code are disproportionately light when compared to the relevant crimes. However, there is no guarantee of effective justice under the informal regime. The consequent weakness of these two regimes encourages reliance on jurisdictions under Taliban control.